Quality of family planning counseling and associated factors among women attending family planning clinics at selected health centers in Akaki Kality sub-city, Addis Ababa, Ethiopia - Goyomsa, Girma Garedew; Geleta, Leta Adugna; Debela, Sisay Abebe; Reshid, Nejiba; Ogeto Luke, Amana; Lamaro Abota, Tafesse; Girma, Derara; Dejene, Hiwot (Frontiers in Global Women's Health, 2022)
Background: Ethiopia has achieved a remarkable improvement in the provision of family planning. Modern contraceptive prevalence rate has shown a five-fold increment in the last two decades. Yet, the family planning service in the country is still deficient and characterized by poor counseling quality. Objective: to assess the quality of family planning counseling provided and the associated factors at selected health centers in Addis Ababa, Ethiopia. Method: A cross-sectional study was conducted among 678 randomly selected women attending family planning services at health centers in Addis Ababa, Ethiopia. Multivariable logistic regression was performed to identify factors associated with the quality of family planning counseling. Result: A total of 678 women participated in the study. About 29.1%; 95% CI: [25.7%, 32.6%] of the respondents were adequately counseled. Age groups 37 - 49 [AOR=2.7; 95% CI 1.1, 6.6], being in marital union [AOR=2.8; 95% CI 1.2, 6.7], attaining secondary educational [AOR=1.9; 95% CI: 1.1, 3.6] or higher educational [AOR=2.2; 95% CI: 1.2, 4.3] and visit status [AOR=1.6; 95% CI: 1.1, 2.4] were significantly associated with good counseling. Conclusion: Less than one in three women was counseled adequately. Health professionals should give due attention to younger age women, single and clients with their first presentation to the health facility. It also indicates that promoting education among Ethiopian women is very crucial for a positive outcome of family planning counseling.